Comparison eCAP and behaviour thresholds in post lingual medel cochlear implant users (Annals of Medical Research, 2021)
Aim: Our purpose with this study is to determine the most effective and suitable cochlear implant programming method for CI users’ implants to experience quality hearing and for the users to achieve efficiency from their implants.Materials and Methods:Twenty-five cochlear implant users with post lingual progressive hearing loss were included in the study. Twelve electrodes’ ART (auditory nerve response telemetry) thresholds were determined and were statistically analyzed to be evaluated in the study. For 12 electrodes whose AutoART threshold was determined, the MCLs (most comfortable loudness) were determined behaviorally.Results: No correlations were found between the 12 electrodes and AutoART. It was seen that there was a correlation between the pure tone average obtained from 500-1000-2000 and 4000Hz and the speech reception threshold.Conclusion: The use of two test batteries together to determine thresholds can be helpful in the programming of the speech processor. The more audiologists work with cochlear implant patients and do programming, the more they accumulate data and gain occupational experience. With the occupational experience acquired in this manner, more accurate programming can be done.
Keywords: Behavioral test; cochlear implant; eCAP; subjective test; objective test